Buddhist Perspectives on Interfaith Relations - Sek, Piseth (Journal of Buddhist Education and Research (JBER), 2017)
Religions should not be the tool to divide people, but should be used to bring unity. In this sense, there should be an urgent call for every follower of different beliefs to come and discuss together to avoid misunderstanding among religions. This is when people, regardless of religions, work to promote interreligious relations and mutual understandings. As we like to put it, we are working to encourage interfaith relations. In the case of interfaith relations, Buddhism should be one of the tools to bring the people of different faiths closer. Buddha has been a great role model of interreligious work. So there are some understanding Buddhists today. If we want to unite people from different faiths, Buddhism should have its place in the interfaith work.